A facile strategy to construct layered membranes with high and stable proton conductivity based on sulfonated graphene oxide. (15th October 2021) - Jin, Jin; Jia, Jing; Song, Di; Wang, Ning; Liu, Ke; Zuo, Tingting; Che, Quantong
Summary: Spin coating as an easy‐operation strategy to construct layered membranes has been widely mentioned in the fields of microelectronics, energy storage, and conversion, etc. In this research, the successful construction of proton exchange membranes (PEMs) bearing layered structure consisting of sulfonated graphene oxide (SGO) nanosheets and polyvinyl chloride (PVC) with the spin coating method has been demonstrated by the identification of the multilayered dispersion of components and compact structure. The hydrophilic SGO nanosheets could increase the hydrophilicity of composite membranes since they bore a large number of polar oxygen functional groups. Phosphoric acid (PA) can be combined through the formed intermolecular hydrogen bonds between PA molecules and SGO nanosheets. The content of PA in PEMs can be adjusted by controlling the concentration of PA solutions, immersion temperature, and duration time. A comparative study with the membrane from the solution casting method has been performed, expecting to understand the influence of layered structure on membrane performance. It was found that the well‐ordered distribution of SGO nanosheets facilitated proton conduction, demonstrating from the proton conductivity of 3.63 × 10 −2 S/cm at 150°C. The fine proton conductivity stability, for instance, the result of 2.71 × 10 −2 S/cm at 140°C lasting 1000‐hour supported the component stability and mechanical strength. The research revealed that the spin coating technique could provide a facile and effective strategy to construct well‐ordered membrane electrolytes for the application of high‐ temperature proton exchange membrane fuel cells. Abstract : 1. Multilayered proton exchange membranes based on sulfonated graphene oxide were constructed. 2. A 1000‐hour proton conductivity was 2.71×10 ‐2 S/cm at 140 °C. 3. The maximum tensile stress reached 12.8 MPa.